Partial purification of adeno-associated virus Rep78, Rep52, and Rep40 and their biochemical characterization. - Im, D S (1992)
We have used differential cell extraction and conventional chromatography to separate and partially purify the four adeno-associated virus (AAV) nonstructural proteins Rep78, Rep68, Rep52, and Rep40. In the cytoplasmic extracts Rep52 and Rep40 were present in greater abundance than Rep68 and Rep78, with Rep78 being the least abundant. In nuclear extracts the four Rep proteins were approximately equal in abundance. Regardless of the subcellular fraction examined, three of the Rep proteins (Rep78, Rep68, and Rep40) consisted of two protein species with slightly different mobilities during polyacrylamide gel electrophoresis. In contrast, Rep52 consisted of only one protein species. Both Rep78 and Rep68 were capable of binding efficiently to AAV terminal hairpin DNA substrates, but we could not detect site-specific DNA binding by Rep52 and Rep40. Like Rep68, Rep78 had both an ATP-dependent trs endonuclease and a DNA helicase activity. Both Rep78 and Rep68 cut the terminal AAV sequence at the same site (nucleotide 124). The binding, trs endonuclease, and DNA helicase activities comigrated during sucrose density gradient centrifugation with a mobility expected for a monomer of the protein, suggesting that the three biochemical activities were intrinsic properties of the larger Rep proteins. The chromatographic behavior and the DNA-binding properties of the four Rep proteins identified at least two domains within the rep coding region, an exposed hydrophobic domain within the C-terminal end (amino acids 578 to 621) and a region within the N terminus (amino acids 1 to 214) which was necessary for binding to the terminal repeat sequence. No site-specific nuclease activity was seen in the presence of nucleotide analogs ATP-gamma-S or AMP-PNP, suggesting that ATP hydrolysis was required for the endonuclease reaction. Furthermore, although ATP was the only cofactor which would support the trs endonuclease activity of Rep78, Rep68 nuclease activity was seen in the presence of several other nucleotide cofactors, including CTP, GTP, and UTP.